Sleep problems in infancy and early school age in very preterm infants. (October 2022) - Neitmann, Johanna; Hanke, Kathrin; Humberg, Alexander; Siller, Bastian; Spiegler, Juliane; Juhnke, Karla; Gilmore, Jessica; Odendahl, Rainer; Herting, Egbert; Göpel, Wolfgang; Härtel, Christoph; Fortmann, Ingmar; et al.
Abstract: Background: Sleep plays an important role for psychological and physical health, especially in infants at high risk for long-term neurodevelopmental impairment such as preterm infants. Objective: Our study aimed at determining risk factors for long-term sleep impairment in very-preterm (VPT; <32 weeks of gestation) infants. Methods: Sleep problems were analyzed in an observational study in infants of the German Neonatal Network born between January 1st 2009 and December 31st 2014. Parental questionnaires of n = 2928 VPT children were evaluated regarding the child's sleep behavior at five years of age. Univariate and logistic regression analyses were used to identify risk factors for delayed sleep onset and hyperactivity/inattention (Strength and Difficulties Questionnaire) . In a second cohort of n = 342 VPT infants, sleep habits were evaluated at toddlers age via the Infant Sleep Questionnaire . Results: In our cohorts, 424/2928 (14.5 %) preterm children were diagnosed with delayed sleep onset at early school age while 57/342 (16.7 %) had sleep impairment in early infancy. Gestational age was not independently associated with sleep problems (i.e., early school age: OR 0.97, 95 % CI 0.9–1.1, p = 0.15). Notably, in both our cohorts, neonatal exposure to analgesics and sedatives was associated with a higher risk for sleep problems, i.e., early school age: exposure to sedatives: OR 1.31, 95%CI 1.02–1.7, p = 0.03. Sleep problems and drug exposure were both associated with hyperactivity/inattention. Conclusion: Sleep problems of VPT children are unrelated to gestational age which suggests rather individual risk factors. The significant neonatal exposure to analgesics and sedatives may contribute to long-term sleep impairment. Highlights: sleep problems of VPT children are unrelated to gestational age individual strategies are needed to approach sleeping behavioral problems in preterm children the exposure to analgesics and sedatives during primary hospital stay is associated with long-term sleep impairment sleep problems and the exposure to analgesics and sedatives are associated with hyperactivity and inattention sleep problems of VPT children are associated with neurodevelopmental impairment (decreased IQ and motor function)